Medieval and Early Modern Afterlives - (:unkn) unknown (Universitatverlag WINTER Heidelberg, 2023)
This introductory essay engages with the content and argument of the volume’s essays, reflects on the language, labels and period boundaries used to define medieval and early modern studies, and analyses the cover image to consider the longue durée of books and ways in which editors and the book trade have shaped textual and authorial afterlives.
Keywords: Medieval; Early Modern; Book History; Periodisation